Régimen de humedad del suelo de páramo y su relación con las prácticas socioculturales en el caserío San Jorge, cantón Patate, 2021. - Abril Terán, Erik Ismael (2022)
Socio-cultural practices such as overgrazing, the burning of natural vegetation, urbanization, and the expansion of the agricultural frontier have transformed a large area of the Andean landscape, causing loss of biodiversity, soil degradation, and the deterioration of the natural functions of these ecosystems. Therefore, this research aims to determine the relationship between the moisture regime of the paramo soil and the socio-cultural practices in "Caserío San Jorge," Patate canton, in 2021. So, the application of interviews and surveys are based on the diagnosis of socio-cultural practices, external species, and the determination of the current knowledge of the population of the area in terms of the moor ecosystem. After this, through the implementation of the soil sampling methodology proposed by the current environmental regulations, a total of 120 soil samples were collected (intervened and non-intervened), of which 40 made up two composite samples, and 80 were analyzed separately independently. Once the appropriate samples were collected, the physical-chemical characterization of the same was carried out through the support of the INIAP laboratories and the use of the laboratories at the Technical University of Cotopaxi, determining the key indicators of soil quality showing a loss of 20.25% of the water retention capacity of the soil due to human intervention was delimited in winter and 18.73% in summer. Finally, the T-test was implemented for related samples, determining with 95% statistical certainty that there is a direct relationship between socio-cultural practices and the capacity of the paramo soil to store water resources and a variation of 38.08% in the chemical quality indicators of the soil. Therefore, traditional productive practices, livestock activities, and the indiscriminate introduction of species are degrading the soil of the paramo and, as a result, interfering with its natural functions.